Biomedical applications of diamond-like carbon coatings: A review - Roy, Ritwik Kumar; Lee, Kwang-Ryeol (WILEY-LISS, 2007)
Owing to its superior tribological and mechanical properties with corrosion resistance, biocompatibility, and hemocompatibility, diamond-like carbon (DLC) has emerged as a promising material for biomedical applications. DLC films with various atomic bond structures and compositions are finding places in orthopedic, cardiovascular, and dental applications. Cells grew on to DLC coating without any cytotoxity and inflammation. DLC coatings in orthopedic applications reduced wear, corrosion, and debris formation. DLC coating also reduced thrombogenicity by minimizing the platelet adhesion and activation. However, some contradictory results (Airoldi et al., Am J Cardiol 2004;93:474-477, Taeger et al., Mat-wiss u Werkstofftech 2003;34:1094-1100) were also reported that no significant improvement was observed in the performance of DLC-coated stainless stent or DLC-coated femoral head. This controversy should be discussed based on the detailed information of the coating such as atomic bond structure, composition, and/or electronic structure. In addition, instability of the DLC coating caused by its high level of residual stress and poor adhesion in aqueous environment should be carefully considered. Further in vitro and in vivo studies are thus required to confirm its use for medical devices. (c) 2007 Wiley Periodicals, Inc.
Keywords: IMMERSION ION-IMPLANTATION; A-C-H; PROSTHETIC JOINT MATERIALS; TOTAL HIP-REPLACEMENT; DLC-COATINGS; IN-VITRO; AMORPHOUS-CARBON; ORTHOPEDIC APPLICATIONS; THIN-FILMS; TRIBOLOGICAL PERFORMANCE